ASSESSING BIOTERRORISM PREPAREDNESS IN INDONESIA: CHALLENGES AND STRATEGIC FRAMEWORKS FOR NATIONAL SECURITY - Toni, Toni; Haliansyah, Haliansyah (UI Scholars Hub, 2025)
Bioterrorism represents a growing global threat, necessitating robust preparedness frameworks to safeguard national security. This study aims to assess Indonesia's bioterrorism preparedness by identifying key challenges and proposing strategic frameworks for improvement. Using Structural Equation Modeling (SEM), this quantitative research examines the relationship between Government Capacity (independent variable), Crisis Management Effectiveness (intervening variable), and National Security Preparedness (dependent variable). A structured survey was distributed to key stakeholders, including public health officials, security experts, and policymakers, yielding 100 valid responses. Data analysis through SEM revealed that Government Capacity significantly influences Crisis Management Effectiveness, which in turn positively impacts National Security Preparedness. Moreover, Crisis Management Effectiveness partially mediates the relationship between Government Capacity and National Security Preparedness, highlighting its critical role as an intervening factor. The findings underscore the importance of enhancing government capacity through investments in biosecurity infrastructure, interagency coordination, and public health training. Strengthening crisis management mechanisms can amplify national security preparedness against bioterrorism threats. The study concludes with recommendations for targeted policy interventions and collaborative frameworks to bolster Indonesia's resilience to bioterrorism.